Seizure occurrence in FCD type II is predicted by lesion position and linked to cytoarchitectural alterations - Procházková, Natálie; Olson, Carl Václav Lím; Shariati, Niki; Rozlivková, Jana Thao; Populová, Jana; Řehořová, Monika; Kudláček, Jan; Jiruška, Přemysl; Novák, Ondřej (Acta neuropathologica communications, 2025)
Focal cortical dysplasia (FCD) is a common malformation of cortical development and a major cause of early-onset, drug-resistant epilepsy. FCD type II is defined by abnormal lamination, altered cellular composition, and pathological cells, notably dysmorphic neurons (DNs) and balloon cells. DNs are thought to drive epileptogenicity through both cell-autonomous and non-cell-autonomous mechanisms, the latter including not only aberrant connectivity but also indirect modulation of excitability in local cell populations. We performed a multiscale structural and morphological analysis to elucidate the basis of FCD epileptogenicity and the impact of somatic mTOR mutations during brain development. Using a mouse model of FCD type II, we show that lesions in frontal and motor cortical regions are the strongest predictors of spontaneous seizure occurrence. This localization-dependent epileptogenicity offers an experimental explanation for the higher clinical epileptogenicity of frontal FCDs and suggests that posterior lesions may remain silent-an open question in human pathology. In our model, FCD tissue displayed considerable expansion, with cortical thickness up to ~ 20% in seizure-bearing animals. This expansion coincided with an overall ~ 40% reduction in neuronal density, consistent with tissue hypertrophy. DN density did not differ between seizure and non-seizure animals, challenging the notion that higher DN load directly predicts epileptogenesis. At the microscopic level, we describe DN axonal pathologies, including giant varicosities. In the cortex, these appeared as vesicle-filled boutons, whereas along callosal axons they were frequent but largely empty. Bouton density was markedly reduced in FCD cortex. Together, these findings leave the net synaptic effect of dysmorphic neurons unresolved, challenging the assumption that axonal hypertrophy translates into increased excitatory drive. While morphological abnormalities in FCD type II are well documented, their functional consequences remain incompletely understood. Here, we used macro- and microscopic structural features of FCDII to assess seizure susceptibility, providing new insights into epileptogenesis.
Keywords: Mice; Lesion topography; záchvaty; myši transgenní; Brain; Focal cortical dysplasia type II; Seizures; Cytoarchitecture; Disease Models, Animal; modely nemocí na zvířatech; TOR Serine-Threonine Kinases; epilepsie; Male; Malformations of Cortical Development, Group I; myši; Somatostatin interneurons; neurony; TOR serin-threoninkinasy; Mice, Inbred C57BL; Epilepsy; ženské pohlaví; malformace mozkové kůry, skupina I; Predictive parameters; Mice, Transgenic; mužské pohlaví; Neurons; myši inbrední C57BL; mozek; Animals; Parvalbumin interneurons; zvířata; Female; Axonal varicosities